2021
DOI: 10.1080/23311932.2021.1913843
|View full text |Cite
|
Sign up to set email alerts
|

Variations in nutrient composition of oyster nuts (Telfairia pedata) across different agro-climatic conditions

Abstract: In sub-Saharan Africa, nutrient deficiency remains a challenge. The challenge is partly due to the underutilization of available local nutrient sources and failure to optimize nutrients based on agro-climatic conditions. This study investigated the nutrient composition and variations in the underutilized oyster nuts (Telfairia pedata) from different sites and elevation levels encompassing different agro-climatic conditions. Fats were the most abundant contents of the nuts with 68%, followed by 25% protein, 5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
2
1
Order By: Relevance
“…This may be attributable to the plant's geographical location and the research's analytical accuracy. However, the 3.09±0.93 percentage moisture content of Telfairia pedata (Oyster Nut) seeds obtained by Mwakasege et al [15] is about five-fold less than what was obtained in this study. The result shows that the leaves significantly differ in percentage moisture content at (P < 0.05).…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…This may be attributable to the plant's geographical location and the research's analytical accuracy. However, the 3.09±0.93 percentage moisture content of Telfairia pedata (Oyster Nut) seeds obtained by Mwakasege et al [15] is about five-fold less than what was obtained in this study. The result shows that the leaves significantly differ in percentage moisture content at (P < 0.05).…”
Section: Resultscontrasting
confidence: 82%
“…Additionally, when subjected to roasting, these seeds exhibit a flavour reminiscent of almonds. Telfairia pedata is a native forest food plant in the Uluguru North and West Usambara Mountain regions, known for providing edible nuts and seeds [9]. The seeds of Telfairia pedata are utilised in tropical East Africa for oil production and are subjected to roasting and consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Most phenolic compounds exhibit antioxidant activities (Kumar et al, 2016). Isaiah et al, (2021), reported the physico-chemical and antioxidant properties of Kenyan T. pedata seeds extract, and Mwakasege et al, (2021a), also reported the nutritional variability of the seeds of T. pedata collected from the agro forests of Kilimanjaro Mountain, Arusha and Tanga. This paper, however, gives a detailed analysis of the nutritional, minerals, phenolics and fatty acids compositions of T. pedata seed kernels collected from Chekereni, Kilimanjaro, thus, revealing their potential in industrial development and health maintenance.…”
Section: Introductionmentioning
confidence: 99%